2014
DOI: 10.1371/journal.pone.0105812
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Mouse Germinal Vesicle Stage Oocyte Quality by Evaluating the Cumulus Layer, Zona Pellucida, and Perivitelline Space

Abstract: To improve the outcome of assisted reproductive technology (ART) for patients with ovulation problems, it is necessary to retrieve and select germinal vesicle (GV) stage oocytes with high developmental potential. Oocytes with high developmental potential are characterized by their ability to undergo proper maturation, fertilization, and embryo development. In this study, we analyzed morphological traits of GV stage mouse oocytes, including cumulus cell layer thickness, zona pellucida thickness, and perivitelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 53 publications
3
11
0
Order By: Relevance
“…It is well known that optimal cumulus cell expansion is essential for normal oocyte maturation, oocyte cytoplasmic maturation in particular [45,46]. Impaired cytoplasmic maturation was associated with poor cumulus cell development [45,47]. The data in this study showed that cumulus cell expansion reached a maximum, with visible corona radiata, after 4RI biphasic IVM.…”
Section: Discussionmentioning
confidence: 51%
“…It is well known that optimal cumulus cell expansion is essential for normal oocyte maturation, oocyte cytoplasmic maturation in particular [45,46]. Impaired cytoplasmic maturation was associated with poor cumulus cell development [45,47]. The data in this study showed that cumulus cell expansion reached a maximum, with visible corona radiata, after 4RI biphasic IVM.…”
Section: Discussionmentioning
confidence: 51%
“…The formation of junctional complexes between the oocyte and granulosa cells begins during the transition of primordial follicles to primary-secondary follicles when the zona pellucida (ZP) glycoproteins are secreted and form a matrix between oocyte and granulosa cells 25 . Although a perivitelline space appears between the ZP and the oocyte cell membrane 26,27 , transzonal projections (TZPs) form between the oocyte and granulosa cells and are physiologically and functionally critical for follicular survival 28,29 . One of the components of TZPs is connexon, a hexamer of connexin37 (Gja4), which restricts gap junctional communication transport to factors with a molecular weight lower than 1,000 Da 30 .…”
Section: Discussionmentioning
confidence: 99%
“…ZP thickness in individual preembryos has been proposed to be a marker of normal human preembryo development because a correlation was observed between ZP thickness and implantation of thawed as well as fresh preembryos [26,27]. A thinner portion of the zona pellucida is very likely necessary for appropriate hatching during the blastocyst stage.…”
Section: Discussionmentioning
confidence: 99%